KAJIAN TENTANG KARAKTERISTIK KELUARGA DAN POLA PEMBERIAN MPASI DAN HUBUNGANNYA DENGAN STATUS GIZI ANAK BALITA - Wahyuni, Sri; Djamilus, Fauzia; Samsiah, Samsiah; Mulyati, Sri; Astuti, Maya; Sasnitiari, Ni Nyoman; Permanik, Novita Dewi; Widiawati, Ida; Handayani, Ida Farida (Poltekkes Kemenkes Bandung, 2024)
The introduction of solid, semi-solid or soft foods is positively associated with nutritional status and reduces the likelihood of stunting. The results of the Indonesian Nutrition Status Survey in 2022 showed that the prevalence of stunting in Indonesia still reached 21.6%. West Java Province has a stunting prevalence of 20.2%, while in Bogor City it is still 19.3%. The purpose of the study was to analyze the relationship between family characteristics, complementary feeding patterns and the nutritional status of toddlers. The research design used a mix method (quantitative and qualitative). Quantitative research with a cross-sectional approach and qualitative research with indepth interviews (exploring complementary feeding patterns, problems, handling and educational needs related to complementary feeding). The qualitative exploration result were analyzed using deductive thematic. The study population was all toddlers aged 12-60 months in Bogor City, the sample size was 120 with purposive sampling. Statistical tests used chi-square test and Mann-whitney test. The results showed a significant relationship between family characteristics and patterns of complementary feeding with the children’s nutritional status under five. The results of qualitative exploration showed there were four themes, namely First, social and cultural and adverse beliefs. Second, lack of knowledge, Third, the environment (home and residence) is less supportive. Fourth, poor economy. The research concluded that there was a relationship between family characteristics and patterns of complementary feeding with the nutritional status of children under five. Efforts are needed to overcome the problem of stunting through education about complementary feeding.